2021
DOI: 10.1002/mnfr.202001175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hesperidin Consumption on the Cardiovascular System in Pre‐ and Stage 1 Hypertensive Subjects: Targeted and Non‐Targeted Metabolomic Approaches (CITRUS Study)

Abstract: The aim of the present work is to determine new biomarkers of the biological effects of hesperidin in orange juice (OJ) applying a non-targeted metabolomics approach validated by targeted metabolomics analyses of compliance biomarkers. Methods and Results: Plasma/serum and urine targeted (HPLC-MS/MS) and untargeted ( 1 H-NMR) metabolomics signatures are explored in a subsample with pre-and stage-1 hypertension subjects of the CITRUS study (N = 159). Volunteers received 500 mL day −1 of control drink, OJ, or he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Supplementation with the citrus polyphenols hesperidin and naringin led to decreases in inflammatory markers produced by peripheral blood mononuclear cells in obese cats [27]. In the CITRUS trial in humans, consumption of orange juice supplemented with 600 mg hesperidin for 12 weeks appeared to result in the downregulation of six proinflammatory genes [28], decreased blood pressure [29], and lowered levels of several uremic toxins in the urine [30]. Other randomized, double-blind clinical trials showed that consumption of flavonoid-rich orange juice benefitted cognitive function in middle-aged [31] and older adults [32].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with the citrus polyphenols hesperidin and naringin led to decreases in inflammatory markers produced by peripheral blood mononuclear cells in obese cats [27]. In the CITRUS trial in humans, consumption of orange juice supplemented with 600 mg hesperidin for 12 weeks appeared to result in the downregulation of six proinflammatory genes [28], decreased blood pressure [29], and lowered levels of several uremic toxins in the urine [30]. Other randomized, double-blind clinical trials showed that consumption of flavonoid-rich orange juice benefitted cognitive function in middle-aged [31] and older adults [32].…”
Section: Discussionmentioning
confidence: 99%
“…Citrus flavonoids are well-known for their beneficial effects at the cardiovascular and cardio-metabolic level [ 1 ]. Recently, daily hesperidin supplementation was shown to improve the blood pressure in pre- and stage 1 phase hypertensive patients [ 2 ]. Likewise, the Citrus flavonoids naringin and naringenin, the latter being the aglycone of naringin, are promising nutraceuticals in the strategy regarding the management of cardiovascular complications, improving the systolic pressure levels and the metabolic profile [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed blood pressure reduction and anti-inflammation. 10 Scoparone shows a PPARγ antagonic effect in 3T3-L1 preadipocyte differentiation suppression as researchers at University of Science and Technology in Korea shift their attention to obesity, using real time-PCR analysis which indicated down-regulated adipogenic genes. 11 Problems with the chemical profile of Traditional Chinese medicines threaten to create a chasm between the quality assessment of herbal medicine and their clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Pla-Pagà and his colleagues performed a metabolomic analysis suggesting that hesperidin potentially showed a beneficial cardiovascular effect by impacting the serum metabolomic profile based on the levels of urine and plasma metabolite, hesperidin 7- O -β- d -glucuronide, obtained from pre- and stage-1 hypertension patients who received 500 mL hesperidin-containing orange juice per day. The results showed blood pressure reduction and anti-inflammation . Scoparone shows a PPARγ antagonic effect in 3T3-L1 preadipocyte differentiation suppression as researchers at University of Science and Technology in Korea shift their attention to obesity, using real time-PCR analysis which indicated down-regulated adipogenic genes …”
Section: Introductionmentioning
confidence: 99%